Concentrator Location in Telecommunications Networks - Yaman, Hande (Combinatorial Optimization, 2005)
The author presents polyhedral results and exact solution methods for location problems encountered in telecommunications but which also have applications in other areas like transportation and supply chain management. Audience This volume is suitable for researchers and practitioners in operations research, telecommunications, location theory and integer programming.